Analisis Rasio Keuangan Untuk Memprediksi Financial Distress Perusahaan Manufaktur Di BEI - Kurniadi, Akhmad (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to examine the prediction of the company's financial difficulties using the Altman Z-score 1968 model and the effect of financial ratios including working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, market value equity to book value. of total liabilities, and sales to total assets on financial distress. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) 2015-2019. Sampling in this study using purposive sampling method and obtained 64 companies. The results showed that the variables Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Tax to Total Assets (X3), Market Value Equity To Book Value of Total Liabilities (X4), and Sales to Total Assets (X5) has a positive effect on financial distress, and the most significant effect on financial distress is the variable Retained Earnings to Total Assets. From the results of SPSS 17.0 processing, the equation Z = -1,813 + 1,216 X1 + 1,837 X2 + 0.122 X3 + 0.070 X4 + 0.506 X5 is produced. Meanwhile, the discriminant model that was formed had a high enough validation rate, namely 97.6%. Keywords: Financial ratio analysis; Financial distress; Altman Z-score